Characterization of Obese Phenotypes in a Small Nonhuman Primate, the Common Marmoset (Callithrix jacchus) - Suzette D. Tardif; Michael L. Power; Corinna N. Ross; Julienne N. Rutherford; Donna Layne‐Colon; Mark Paulik (2009)
This report explores aspects of developing obesity in two captive populations of common marmosets (Callithrix jacchus), a small primate with a short lifespan that may be of value in modeling chronic aspects of obesity acquisition and its lifetime effects. Two populations were examined. In study 1, body composition, lipid parameters, and glucose metabolic parameters were measured in a population of 64 adult animals. Animals classified as obese (>80th percentile relative fat based on sex) displayed both dyslipidemia (higher triglyceride and very low-density lipoprotein (VLDL)) and altered glucose metabolism (higher fasting glucose and HbA(1c)). Using operational definitions of atypical values for factors associated with metabolic syndrome in humans, five subjects (7.8%) had at least three atypical factors and five others had two atypical factors. A previously unreported finding in these normally sexually monomorphic primates was higher body weight, fat weights, and percent fat in females compared to males. In a second study, longitudinal weight data for a larger population (n = 210) were analyzed to evaluate the development of high weight animals. Differences in weights for animals that would exceed the 90th percentile in early adulthood were evident from infancy, with a 15% difference in weight between future-large weight vs. their future-normal weight litter mates as early as 4-6 months of age. The marmoset, therefore, demonstrates similar suites of obesity-related alterations to those seen in other primates, including humans, suggesting that this species is worthy of consideration for obesity studies in which its fast maturity, high fertility, relatively short lifespan, and small size may be of advantage.